2018
DOI: 10.12714/egejfas.2018.35.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Estimating gillnet selectivity of Bluefish (Pomatomus saltatrix) by morphology

Abstract: The dataset of the study consists of total length, fork length, head girth, maximum girth and weight measurements of 136 bluefish. The relationship between the total length and fork length of the product was TL=1.1348×FL0.8184; the relationship between the total length and weight was W=0.0103×L 2.97. The relationships between the total length and head girth and between the total length and maximum girth of the sample were linear: the relationship of the total length and head girth was Ggill=0.5092×TL0.0874; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…For bluefish, six of fourteen studies had significantly different bvalues, which reported negative allometric growth (Kalaycı et al, 2007;Bök et al, 2011) and isometric growth (Kasapoğlu and Düzgüneş, 2014;Bal et al, 2015Bal et al, , 2018İlkyaz, 2018). Nevertheless, bluefish in the present study showed the b-values to be generally in agreement with similar results (positive allometric) in other studies (Table 1).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…For bluefish, six of fourteen studies had significantly different bvalues, which reported negative allometric growth (Kalaycı et al, 2007;Bök et al, 2011) and isometric growth (Kasapoğlu and Düzgüneş, 2014;Bal et al, 2015Bal et al, , 2018İlkyaz, 2018). Nevertheless, bluefish in the present study showed the b-values to be generally in agreement with similar results (positive allometric) in other studies (Table 1).…”
Section: Resultssupporting
confidence: 87%
“…Most of the studies on bluefish has been carried out in the Marmara Sea and Aegean Sea. Some of them is about age, growth, maturity, fishing gear selectivity of bluefish (Ceyhan and Akyol, 2006;Akyol and Ceyhan, 2007;Ceyhan et al, 2007;Acarlı et al, 2013Acarlı et al, , Öztekin et al, 2018Bal et al, 2018;İlkyaz, 2018). However, there are only few studies on bluefish in the Black Sea.…”
Section: Introductionmentioning
confidence: 99%
“…For example, beam trawls are extremely destructive to benthic biodiversity and compromise ecological integrity, whereas sprat (although not consumed by humans) are extremely important to trophic structure function in their role as prey species for predatory fish. They are major prey item (39%; Işmen and Bingel, 2000) for whiting, which in turn is a major prey item (61.7%) for turbot (Zengin, 2000;Solberg et al, 2015). In fact, turbot and whiting fisheries have collapsed due to the intense sprat fisheries which recently developed in the last 25 years (Zengin and Gümüs, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The factors influencing changes to MLS regulations are not publicly known (Yildiz and Ulman, 2020). In Turkish waters, bluefish reach sexual maturity between 26.5 cm (Atılgan et al, 2016) and 28 cm TL (Ceyhan et al, 2007;Ilkyaz, 2018).…”
Section: Speciesmentioning
confidence: 99%
“…Throughout these migrations' bluefish have been highly exploited, especially in area of western Black Sea and Marmara Sea (Ceyhan and Akyol 2006). Because of the commercial importance of bluefish, most of the studies were focused on age determination (Ceyhan et al, 2007), growth parameters (Cengiz et al, 2013), length-weight relationshisps (Özpiçak et al, 2017;Cumplido et al, 2018), diet (Buckel et al, 2004;Lucena et al, 2006), otolith size-length relationships (Cengiz et al, 2012;Zengin et al, 2017;Bal et al, 2018a), selectivity (Acarlı et al, 2013;İlkyaz, 2018) and morphometric variation (Turan et al, 2006). On the other hand, there are limited studies about stock structure of bluefish (Graves et al, 1992).…”
Section: Introductionmentioning
confidence: 99%